Developing a social participation model in Iran's sports for all - Javadipoor, M.; Zareian, H.; Parsaju, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The present study aims to design a social participation model in Iran's sports for all. Based on the exploratory nature of the research subject, the study method was qualitative and a grounded theory strategy was carried out to design a social participation model in Iran's sports for all. Sampling was purposive and had a snowball method. The theoretical saturation was obtained after 27 deep and semi-structured interviews with knowledgeable experts, and then major categories were extracted after completing a coding process. Results of open coding revealed that 811 initial indicators and 184 final indicators determined causal, underlying and intervening conditions, strategies and consequences of social participation in Iran's sports for all. Final indicators were classified into 63 concepts and 28 categories in the axial coding, and finally identified categories resulting from selective coding explained a social participation model in Iran's sports for all.